A Commentary on the Special Issue: Promoting Use of Positive Reinforcement in Schools. (August 2020) - Nelson, C. Michael; Kauffman, James M.
In this commentary on the Beyond Behavior special issue: In Support of Positive Reinforcement, the authors ask the question of why myths and misinformation related to positive reinforcement exist. They assert that the principle of negative reinforcement may be one reason. The authors also exhort educators to use the science of behavior analysis as a means to increase the use of positive reinforcement in schools.